1995
DOI: 10.1002/glia.440130204
|View full text |Cite
|
Sign up to set email alerts
|

GFAP‐positive hippocampal astrocytes in situ respond to glutamatergic neuroligands with increases in [Ca2+]i

Abstract: It is becoming increasingly clear that astrocytes play very dynamic and interactive roles that are important for the normal functioning of the central nervous system. In culture, astrocytes express many receptors coupled to increases in intracellular calcium ([Ca2+]i). In vivo, it is likely that these receptors are important for the modulation of astrocytic functions such as the uptake of neurotransmitters and ions. Currently, however, very little is known about the expression or stimulation of such astrocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
121
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(141 citation statements)
references
References 52 publications
15
121
5
Order By: Relevance
“…These observations indicate that glutamate released from depolarized nerve terminals contributes to the correlation of astrocyte Ca 2ϩ activity. This view is also in agreement with data on the functional expression of NMDA and non-NMDA receptors in astrocytes (Porter and McCarthy, 1995;Schipke et al, 2001).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These observations indicate that glutamate released from depolarized nerve terminals contributes to the correlation of astrocyte Ca 2ϩ activity. This view is also in agreement with data on the functional expression of NMDA and non-NMDA receptors in astrocytes (Porter and McCarthy, 1995;Schipke et al, 2001).…”
supporting
confidence: 92%
“…Because the removal of extracellular Ca 2ϩ might deplete intracellular Ca 2ϩ stores, we evaluated the levels of Ca 2ϩ in intracellular stores of astrocytes perfused with nominally Ca 2ϩ -free ACSF by activating IP 3 and ryanodine receptors. To activate IP 3 -mediated Ca 2ϩ release from intracellular stores, we used the metabotropic glutamate receptor agonist t-ACPD (Porter and McCarthy, 1995). Addition of t-ACPD (5 M) to Ca 2ϩ -free ACSF triggered a transient increase of [Ca 2ϩ ] i in 52 of 54 identified astrocytes (two slices from two animals) (Fig.…”
Section: G)mentioning
confidence: 99%
“…Single-cell [Ca2~j 1 recordings then demonstrated that the occurrence of oscillatory [Ca 2~]~responses by the mGluR-specific agonist correlates well with the induction of mGluRS in cultured astrocytes. It has been reported that [Ca2~Iõ scillations are also evoked in cultured astocytes by activation of ionotropic glutamate receptors (Porter and McCarthy, 1995). However, 1 S,3R-ACPD-induced [Ca2~I 1oscillations were blocked solely by the mGluR antagonist, and not by either the AMPA/kainate receptor antagonist or the NMDA receptor antagonist, and did not require calcium in the external medium.…”
Section: Discussionmentioning
confidence: 87%
“…(Bowman et al 2003;Conti et al 1994;Hosli and Hosli 1993;Imura et al 2006;Matthias et al 2003;Miller and Szigeti 1991;Nikcevich et al 1997;Porter and McCarthy 1995;Shao et al 1994;St-Pierre et al 2000;Swanson et al 1997;Venance et al 1998;Whitaker-Azmitia et al 1993;Zhou and Kimelberg 2001). For example, both in vitro and in vivo studies show that the expression of glutamate transporter isoforms GLT-1 and GLAST segregate to different hippocampal GFAP-positive astrocytes (Conti et al 1998;Perego et al 2000;van Landeghem et al 2006).…”
Section: Discussionmentioning
confidence: 99%